Mesenchymal stromal cell therapy for coronavirus disease 2019: which? when? and how much? - Shahani, Pradnya (Cytotherapy, 2021)
Mesenchymal stromal cells (MSCs) are under active consideration as a treatment strategy for controlling the hyper-inflammation and slow disease progression associated with coronavirus disease 2019 (COVID-19). The possible mechanism of protection through their immunoregulatory and paracrine action has been reviewed extensively. However, the importance of process control in achieving consistent cell quality, maximum safety and efficacy—for which the three key questions are which, when and how much—remains unaddressed. Any commonality, if it exists, in ongoing clinical trials has yet to be analyzed and reviewed. In this review, the authors have therefore compiled study design data from ongoing clinical trials to address the key questions of “which” with regard to tissue source, donor profile, isolation technique, culture conditions, long-term culture and cryopreservation of MSCs; “when” with regard to defining the transplantation window by identifying and staging patients based on their pro-inflammatory profile; and “how much” with regard to the number of cells in a single administration, number of doses and route of transplantation. To homogenize MSC therapy for COVID-19 on a global scale and to make it readily available in large numbers, a shared understanding and uniform agreement with respect to these fundamental issues are essential.